2015
DOI: 10.1111/hiv.12206
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis as an independent cause of high immune activation, T‐cell senescence, and lack of immune recovery in virologically suppressed HIV‐1‐coinfected patients

Abstract: ObjectivesDifferent immune alterations have been described in HIV-infected patients with visceral leishmaniasis (VL). We aimed to identify the immunological factors involved in the lack of immunological recovery and VL relapses in HIV-infected patients with VL, by comparison with other HIV-infected patients. MethodsWe carried out a cross-sectional study of 55 patients receiving suppressive combination antiretroviral therapy (cART) for at least 1 year: nine with previous relapsing VL, 20 with an immunodiscordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…In fact, co-infected patients had high percentages of senescent CD4 + and CD8 + T lymphocytes, which reflects chronic immune activation that does not change despite the use of HAART and maintenance of anti- Leishmania treatment. This result is consistent with what has been observed in VL/HIV patients from the Mediterranean basin [30]. Our data confirm this finding through a prospective study design and in patients presenting two distinct clinical outcomes: relapse or no relapse.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, co-infected patients had high percentages of senescent CD4 + and CD8 + T lymphocytes, which reflects chronic immune activation that does not change despite the use of HAART and maintenance of anti- Leishmania treatment. This result is consistent with what has been observed in VL/HIV patients from the Mediterranean basin [30]. Our data confirm this finding through a prospective study design and in patients presenting two distinct clinical outcomes: relapse or no relapse.…”
Section: Discussionsupporting
confidence: 93%
“…The present study confirmed that co-infected patients with active VL (NR or R group) have low CD4 + T cell counts, high levels of cellular activation and microbial translocation and elevated parasitemia. In contrast to a previous study, which evaluated a single parameter [30], herein, the patient’s prior history of VL, the current immunological state of the patient at each visit and the final outcome of therapy during secondary prophylaxis were all taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, assessing the frequencies of cells in exhaustion (CD279 + ), we observed an increase of NK cell frequencies in LbAgS cell cultures in all patient groups when compared with NS cultures, suggesting that NK exhaustion profile might be associated with antigenic specificity. These findings are in agreement with others that correlated the exhaustion status with antigen dependency and persistence, as well as inflammatory process that occur in CL lesions [34][35][36][37].…”
Section: Plos Onesupporting
confidence: 93%
“…in people living with HIV produces pronounced activation of cells from the immunological system and higher production of pro-inflammatory cytokines, turning these cells into targets of the virus and these accelerate the progression to AIDS. 5,6 In some cases, it was observed activation or re-activation of latent infections by Leishmania spp., which occurs in a more immunocompromised stage caused by HIV. 7,8 Visceral leishmaniasis may be diagnosed from classic symptoms such as fever, pallor, and hepatosplenomegaly, associated with a positive serological or parasitological test.…”
Section: Introductionmentioning
confidence: 99%